EVALUATION OF SENSORY CHARACTERISTICS OF SOME ATLANTIC SALMON PRODUCTS IMPORTED TO IRAQ - N. Y. Karim; M. S. Alkhshali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted on salmon(Atlantic salmon)Salmo salar products imported to Iraq, which are a whole fish removed head and tail, fillets, rings, fingers and cubes evaluating of the sensory characteristics of these products and determining their suitability for human consumption. The products were obtained from King of Fish and Meat company ( K.F. M.) , the exclusive agent in Iraq, and all products were within one meal and date, and the validity of each product was from 5/10/2021 to 4/7/2022. Results were as follows: The results of the sensory characteristics (color, flavor, freshness, juiciness, general acceptance) showed asignificant differences (p≤0.05) among salmon fish products, but they did not reach the limits of rejection. The results above of sensory tests of imported salmon fish products showed that they are suitable for human consumption and proved that they are within acceptable limits after comparing them with research and standard specifications.